Penyuluhan Penyakit Diabetes Mellitus kepada Remaja Sekolah Menengah Atas di Jakarta Utara - Yelfi Anwar; Muhammad Dimas An-Naf; Maeesa Putri Lathiifah; Lesli Tiana; Ratih Hardianti; Dewi Puspitasari; Etika Dewi Maharani; Nia Khorotun Fadillah; Fatimah Tibbiya; Lulu Najmah; Kartika Kartika; Jodi Apriadi; Setya Astuti; Alicia Alicia; Naplatul Mahmudah; Indah Mareta Dwi Editia (Jurnal Pengabdian Masyarakat Farmasi : Pharmacare Society, 2022)
Diabetes mellitus counseling is an activity to provide information and education about Diabetes Mellitus (DM) to the community and schools. The counseling was held at the Al-Khariyah High School onsite, the target participants were 11th grade science students. This counseling aims to provide knowledge and understanding of DM and its risk factors, including Body Mass Index (BMI), blood pressure, physical activity habits, frequency of fruit and vegetable consumption, family history of DM, waist circumference (central obesity) in adolescents high school students. The extension activities were carried out for 2 hours, starting with giving a pre-test questionnaire and ending with giving a post-test according to the topic of the extension, each with 10 questions, with the same types of questions. The pre-test and post-test were used to see the presentation of the increase in knowledge and understanding of the extension participants. This training was attended by 26 participants. From the results of the pre-test and post-test answers given, there is an increase in understanding and knowledge about Diabetes Mellitus and risk factors in adolescents.